मानसपटलमा स्थिर बनेका ग्रेगरीसँगका केही पहेलीहरू - Karki, Rajeshwor (Dhaulagiri Journal of Sociology and Anthropology, 2023)
This paper describes the interaction and understanding with Professor Gregory G. Maskarinec.